Antecedents of attitude towards halal cosmetic among Muslim online entrepreneurs in Malaysia : an extension of Theory Planned Behaviour (TPB) model - W Naimatul Asiah binti W Muhamad
The globalization of the halal industry has created more opportunities and business space for entrepreneurs. While this has attracted enormous research interest resulting in commendable extant literature, a dearth of empirical studies focusing on the halal cosmetic section still exists. To fill this lacuna, antecedents of attitude towards online entrepreneurship in halal cosmetic was investigated from the perspective of Muslim online entrepreneurs in Malaysia. Quantitative method was employed in this study. As such, relevant quantitative data were elicited from 327 Muslim online entrepreneurs in Malaysia selected based on purposive sampling. A survey questionnaire that consisted of a combination of newly developed, adapted and adopted items for measurement of variables was used as the research instrument. Data elicited were subjected to both descriptive and inferential statistical analyses. While the data cleaning, descriptive analysis and exploratory factor analysis were conducted via the Statistical Package for Social Sciences (SPSS), the inferential statistics including the confirmatory factor analysis and the full-fledged structural models were carried out via the Analysis of Moment Structures (AMoS) software. Based on a satisfactory global and local model fit assessment criteria the hypothesised model was interpreted as good. The results obtained based on standardized regression weights indicate that halal cosmetic awareness (0.626) and halal cosmetic certification (0.182) both exert statistically significant influence on the attitudes of Muslim online entrepreneurs toward halal cosmetic. Furthermore, a statistically significant effect of attitude of Muslim online entrepreneurs on the intention to adopt halal cosmetic (0.671) in their business was also obtained. As a result, H1, H3 and H5 were supported. On the contrary, results obtained indicate that both halal cosmetic ingredients (0.041) and religiosity (0.007) do not have statistically significant effect on the attitudes of Muslim online entrepreneurs toward halal cosmetic. Due to insignificance in the standardized regression weight, H2 and H4 were therefore not supported. This finding suggests that Muslim online entrepreneur with high level of religiosity but with inadequate knowledge of halal cosmetic ingredients may likely have unfavorable attitude towards halal cosmetic. Finally, as one of the objectives of this dissertation, Cosmetic Entrepreneur Halal Sensitivity Index (CEHSI) guidelines was produced together with a matrix. The research contribution of CEHSI is significant given that it can be a benchmark in halal industry to assess the attitudinal dispositions of the entrepreneurs towards halal cosmetic business.